Compensatory growth and food deprivation in common snook growth performance - Herrera, Leandro Amaral; Silva, Francisco da Costa; Santos, Ana Paula dos; Sousa, Otávio Mesquita de; Sanches, Eduardo Gomes (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effect of food deprivation and the occurrence of compensatory growth on the performance of common snook fingerlings (Centropomus undecimalis). The experiment lasted for 60 days, when fish – 35 individuals per tank – were divided into three groups of treatments, as follows: daily feeding (control); feeding for five days a week, followed by two days of fast; and feeding for four days a week, followed by three days of fast. The treatments of alimentary restriction provided performance indicators significantly inferior to those of the control. Common snook fingerlings should not be subjected to food restriction because of the damages that this practice entails to productive performance.